Pengaruh Kesehatan, Keselamatan Dan Lingkungan Kerja Terhadap Kinerja Karyawan PT. Rajawali I Unit PG. Krebet Baru Bululawang-Malang - Siti Suweibatul Aslamiyah; Hadi Sunaryo; M. Khoirul Anwarudin Broto Suharto (UNIVERSITAS ISLAM MALANG, 2023)
Abstract The purpose of this study is to ascertain how employee performance is impacted by health, safety, and the workplace environment. In this study, a questionnaire was employed to collect data from a sample of 71 employees. Multiple linear analysis with F test and t test assessment of the hypothesis is the analytical approach employed in this investigation. Based on the study's findings, it can be concluded that both health and safety as well as the workplace environment have a positive and significant impact on employees' performance, with the effects of work environment and health and safety having a lesser impact. Keywords: Health, Safety, Work Environment and Employee Performance